Dapagliflozin Binds Specifically to Sodium-Glucose Cotransporter 2 in the Proximal Renal Tubule - Ghezzi, Chiara (J Am Soc Nephrol, 2017)
Kidneys contribute to glucose homeostasis by reabsorbing filtered glucose in the proximal tubules via sodium-glucose cotransporters (SGLTs). Reabsorption is primarily handled by SGLT2, and SGLT2-specific inhibitors, including dapagliflozin, canagliflozin, and empagliflozin, increase glucose excretion and lower blood glucose levels. To resolve unanswered questions about these inhibitors, we developed a novel approach to map the distribution of functional SGLT2 proteins in rodents using positron emission tomography with 4-[(18)F]fluoro-dapagliflozin (F-Dapa). We detected prominent binding of intravenously injected F-Dapa in the kidney cortexes of rats and wild-type and Sglt1-knockout mice but not Sglt2-knockout mice, and injection of SGLT2 inhibitors prevented this binding. Furthermore, imaging revealed only low levels of F-Dapa in the urinary bladder, even after displacement of kidney binding with dapagliflozin. Microscopic ex vitro autoradiography of kidney showed F-Dapa binding to the apical surface of early proximal tubules. Notably, in vivo imaging did not show measureable specific binding of F-Dapa in heart, muscle, salivary glands, liver, or brain. We propose that F-Dapa is freely filtered by the kidney, binds to SGLT2 in the apical membranes of the early proximal tubule, and is subsequently reabsorbed into blood. The high density of functional SGLT2 transporters detected in the apical membrane of the proximal tubule but not detected in other organs likely accounts for the high kidney specificity of SGLT2 inhibitors. Overall, these data are consistent with data from clinical studies on SGLT2 inhibitors and provide a rationale for the mode of action of these drugs.